Peningkatan Kemampuan Siswa dalam Memahami Teks Narrative dengan menggunakan Metode Pembelajaran Role Play pada Siswa Kelas XI IBB di MAN 4 Kediri Semester Genap Tahun Pelajaran 2021/2022 - Andi Sulistio (Lembaga Pengembangan Kinerja Dosen, 2022)
One of the appropriate methods to improve students' abilities is the role play learning method. In improving students' ability to understand students' narrative texts, appropriate learning methods are needed. One of the appropriate methods to improve students' abilities is the role play learning method. The purpose of this study was to analyze the improvement of students' ability in understanding narrative texts using the Role Play Learning Method in Class XI IBB Students in the Even Semester of the 2021/2022 Academic Year. The method used to conduct the research is Classroom Action Research (CAR). The approach used is a qualitative approach. The data collection procedure is the test method. From the test method obtained data in the form of student learning scores which are then used for hypothesis testing. The results of this study are the application of the role play learning method can improve students' ability to understand narrative texts for Class XI IBB students, this can be seen from the students' test scores in the initial test activity from 73.07 increased to 78.20 in cycle 1, and in cycle II increased again to 85. Thus, the role play learning method applied to students can improve students' ability to understand narrative texts for students in Class XI IBB Even Semester in the 2021/2022 Academic Year.